"A Dangerous Black Box:" Idiopathic Hemophagocytic Lymphohistiocytosis in Adult Patients—A Case Report and Review of the Literature. (3rd December 2022) - Agbariah, Nada; Sanz, Javier; Rovó, Alicia
Abstract : Hemophagocytic lymphohistiocytosis (HLH) is a rare potentially life-threatening condition characterized by aberrant inflammation that can be related to genetic or sporadic forms. In both forms, triggering factors may be involved. Early detection of the underlying cause is crucial for therapeutic decision, while early intervention might be associated with better outcomes. The largest descriptions in the literature on HLH refer to pediatric cases. Adolescents and adults may also be affected, but there is scarce evidence regarding their diagnosis and management. We describe here the case of a 68-year-old Swiss woman with HLH, in whom an extensive search for underlying causes was performed, but neither trigger nor pathogenic variant was found. An early intervention first with dexamethasone and later with cyclosporine was performed. The patient showed a favorable response and did not require further hospitalization; however, one year after diagnosis, it was not possible to suspend cyclosporine due to recurrence of laboratory inflammation signs by drug tapering. The occurrence of HLH idiopathic forms represents a challenge; failure to identify the underlying triggering cause generates uncertainty, endless diagnostic investigations, and consequently additional delays in the treatment. This manuscript addresses the difficulties on this issue.